Mātauranga Māori: shaping marine and freshwater futures - Clapcott, Joanne; Ataria, Jamie; Hepburn, Chris; Hikuroa, Dan; Jackson, Anne-Marie; Kirikiri, Rauru; Williams, Erica (New Zealand Journal of Marine and Freshwater Research, 2018)
Keywords: freshwater futures; marine futures; mātauranga māori; policy making; resource development

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

New Zealand Immigration and the Political Economy - Walker, Ranginui J (The Social Contract, 1993)
Keywords: economics; immigration policy; policy making

Indigenous Māori knowledge and perspectives of ecosystems - Harmsworth, Garth R; Awatere, Shaun (Ecosystem services in New Zealand : conditions and trends, 2013)
A framework/model based on Māori knowledge, values and perspectives is presented that distinguishes ‘cultural values’ from ‘cultural services’ and extends the deﬁnition of cultural values across the whole ecosystem services framework. Māori aspirations and well-being are interdependent on ecosystems and ecosystem services. Ultimately Māori wish to use these ecosystem approaches and frameworks to increase participation and inclusion in decision-making, to achieve multidimensional aspirational goals and desired indigenous outcomes.
Keywords: decision making; environment; environmental management; planning; policy making

From hydrology to policy development and implementation: Trends in Aotearoa New Zealand's freshwater management and governance - Fenemor, Andrew; Kirk, Nicholas; Harmsworth, Garth; Taylor, Lara; Weir, Julian; Robson, -Williams Melissa (Journal of Hydrology (New Zealand), 2021)
This section reviews changes to water management and governance in the past ten years. We open with a summary of Aotearoa New Zealand's historical legislative context in regard to rivers, catchments and freshwater resources. We describe the roles of local government, Maori and central government. We detail the growing recognition of tangata whenua values in water management alongside belated development of national policy direction on water quality and allocation. Drawing on the description of modelling advances, we summarise how models are being used in contemporary water management. Finally, we review the implementation of freshwater policy and the integration of science and water policy. In concluding, we argue that integration and implementation challenges must be addressed as hydrologists look beyond 2021 towards future significant legislative changes affecting water and catchment management nationwide.
Keywords: environmental management; policy making; water management